Ответ(ы) на вопрос:
[latex]1) (5x^{2}+8x-7)-(2x^{2}-2x-12)=5x^{2}+8x-7-2x^{2}+2x+12=[/latex]
[latex]=3x^{2}+10x+5[/latex]
[latex]2) 2x-3-2x^{2}-5x-18=-2x^2-3x-21[/latex]
[latex]3)(6a^2-3a+11)-(-3x-a^{3}+7)=6a^2-3a+11+3a+a^{3}-7=[/latex]
[latex]=a^{3}+6a^{2}+4[/latex]
[latex]4)(14ab-9a^{2}-3b^{2})-(-3a^{2}+5ab-4b^{2})=[/latex]
[latex]=14ab-9a^{2}-3b^{2}+3a^{2}-5ab+4b^{2}=9ab-6a^{2}+b^{2}[/latex]
[latex]5) (7xy^{2}-15xy+3x^{2}y)+(30xy-8x^{2}y)=[/latex]
[latex]=7xy^{2}-15xy+3x^{2}y+30xy-8x^{2}y=7xy^{2}+15xy-5x^{2}y=[/latex]
[latex]=xy(7y+15-5x})[/latex]
[latex]6) (\frac{3}{5}m^{3}n^{2}-\frac{1}{4}mn^{2})-(-\frac{5}{8}n^{2}m+\frac{7}{10}m^{3}n^{2})=[/latex]
[latex]=\frac{3}{5}m^{3}n^{2}-\frac{1}{4}mn^{2}+\frac{5}{8}n^{2}m-\frac{7}{10}m^{3}n^{2}=[/latex]
[latex]=m^{3}n^{2}(\frac{3}{5}-\frac{7}{10})+mn^{2}(\frac{5}{8}-\frac{1}{4})=-\frac{1}{10}m^{3}n^{2}+\frac{3}{8}mn^{2}[/latex]
Не нашли ответ?
Похожие вопросы